Analisis Kinerja Anggaran Program Penyelenggaraan Pemilihan, Pengangkatan dan Pemberhentian Kepala Desa : (Studi Kasus pada Dinas Pemberdayaan Masyarakat dan Gampong Kabupaten Aceh Barat) - Windari Sahputri (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the budget program regarding the election, appointment and dismissal of village heads in the Community and Gampong Empowerment Office of West Aceh District. Every government agency in Indonesia has a budget, in accordance with “West Aceh District Regent Regulation Number 53 of 2016 Concerning Position, Organizational Structure, Duties, Functions, and Work Procedures of the Wes Aceh District Community Empowerment and Gampong Office” which states that “Public Empowerment Service and Gampong which is the implementing element of government affairs in the field of community and village empowerment which is the regional authority, where the Community Empowerment Service and Gampong have the task of assisting the regent". This research uses descriptive quantitative method. The type of data used is secondary data, namely LKJIP, RKA, DPA from the results of the documentation. The analysis technique used is Expenditure Variance Analysis and Efficiency Ratio. The results of the study prove that the level of budget performance in the election, appointment and dismissal of village heads at the West Aceh Community and Gampong Empowerment Service based on analysis of spending variance is that the remaining unused budget is IDR 291,275,038.00 or as much as 96% of the total budget set. Based on the Efficiency Ratio analysis, the level of budget efficiency in this program is only 3.75%, which means it is in the less efficient criteria.